2015
DOI: 10.1002/bies.201500063
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's in 3D culture: Challenges and perspectives

Abstract: Summary Alzheimer’s disease (AD) is the most common cause of dementia, and there is currently no cure. The “β-amyloid cascade hypothesis” of AD is the basis of current understanding of AD pathogenesis and drug discovery. However, no AD models have fully validated this hypothesis. We recently developed a human stem cell culture model of AD by cultivating genetically modified human neural stem cells in a three-dimensional (3D) cell culture system. These cells were able to recapitulate key events of AD pathology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
97
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 89 publications
(102 citation statements)
references
References 78 publications
2
97
0
Order By: Relevance
“…Our studies clearly demonstrated the advantage of using human neural cell culture systems in recapitulating Aβ-induced tauopathy, which was not feasible in mouse models 4446 . Our 3D human cellular AD model can also provide a powerful platform for HTS of candidate AD drugs that can reduce Aβ and/or tau pathology in a single system, which is not possible in current AD models (Fig.…”
Section: Clinical Implication Of Human Cellular Models Of Admentioning
confidence: 85%
See 3 more Smart Citations
“…Our studies clearly demonstrated the advantage of using human neural cell culture systems in recapitulating Aβ-induced tauopathy, which was not feasible in mouse models 4446 . Our 3D human cellular AD model can also provide a powerful platform for HTS of candidate AD drugs that can reduce Aβ and/or tau pathology in a single system, which is not possible in current AD models (Fig.…”
Section: Clinical Implication Of Human Cellular Models Of Admentioning
confidence: 85%
“…By generating human neural stem cell lines carrying multiple mutations in APP together with PS1, we achieved high levels of pathogenic Aβ42 comparable to those in brains of AD patients 4446 . Co-expression of multiple FAD mutations in APP and PS1 has been previously employed for generations of various AD transgenic mouse models.…”
Section: Modeling Amyloid Plaques and Nfts In A Human Neural 3d Cultumentioning
confidence: 99%
See 2 more Smart Citations
“…[12] We were able, for the first time, to show both hallmarks of AD in vitro; A β plaques and neurofibrillary tangles, by combining cell genetic manipulation and fluorescence-activated cell sorting (FACS) selection of cells overexpressing the mutated genes. [103] Other research groups have also showed 3D in vitro cell culture models able to partially reproduce AD pathology. In one study, Zhang et al used human neuroepithelial-like stem cells (It-NES) in PuraMatrix hydrogel treated with synthetic A β , [104] and in another study, Choi et al exploited 3D neurospheroids from rat cells in a microfluidic platform treated with synthetic A β .…”
Section: Recapitulating the Human Brain Pathophysiologymentioning
confidence: 99%